EVALUATION OF DISASTER MITIGATION SYSTEM AGAINST LAHAR FLOW OF PUTIH RIVER, MT. MERAPI AREA - T. Maksal Saputra (Journal of the Civil Engineering Forum, 2013)
Merapi mount lies in the border of Yogyakarta and Central Java province. It frequently produces lava sediment deposit in the upper part of the mount, or is called as lava dome. During the rain, the sediment can cause secondary disaster in form of lahar flood, which is potential to produce casualties, especially to the miners working along the river. Kali Putih, that is located in Magelang regency, is the area that undergoes frequents lahar flood that is 125 times in the period of 1931-1996. Meanwhile, there are 5,076 sand miners there. Therefore, it needs an evaluation toward the existing mitigation system that is related to the safety of sand miners.The evaluation is done toward structural mitigation system (Sabo Dam) and non-structural one (e.g. early warning, counseling, and evacuation system). Structural mitigation system is evaluated by comparing the availability of control volume of Sabo Dam to the sediment load during lahar flood, and comparing the travel time of the lahar flood with and without Sabo Dam. Non-structural mitigation system is evaluated by testing the accuracy of the lahar flood estimation chart, and by identifying early warning equipment system installed in field. Interview is also conducted with the miners to see their perception and opinions toward the mitigation.Result of the evaluation shows that the existing early warning system does not produce sufficient time for the sand miners to save themselves. The proposed solution is to divide sand mine area in Putih River into 3 zones, each zone has different procedure of the early warning and evacuation. This is arranged to avoid casualties to the sand miners.Keywords: Lahar flood, sand miners, early warning.